2021
DOI: 10.1002/adsc.202100611
|View full text |Cite
|
Sign up to set email alerts
|

Click Reaction of Selenols with Isocyanates: Rapid Access to Selenocarbamates as Peroxide‐Switchable Reservoir of Thiol‐Peroxidase‐Like Catalysts

Abstract: Selenols react with isocyanates under mild catalyst-free conditions to generate selenocarbamates in good yield and with high selectivity over potentially competing nucleophilic additions. The methodology enables the incorporation of a wide variety of functional groups providing access to a broad array of densely functionalised selenocarbamates. In the presence of competing heteroatom-centered nucleophiles, isocyanates selectively couple with selenols. Selenocarbamates exhibited thiol-peroxidase-like properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…A number of selenium-containing molecules also exhibited remarkable carbonic anhydrase inhibitor activity against different pathogenic bacteria, including Vibrio cholera , Burkholderia pseudomallei , and Mycobacterium tuberculosis [ 40 ]. Over the past years, the synthesis and the study of synthetic or semi-synthetic selenium-containing derivatives has attracted a steadily growing interest amongst organic chemists, medicinal chemists, and biologists [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of selenium-containing molecules also exhibited remarkable carbonic anhydrase inhibitor activity against different pathogenic bacteria, including Vibrio cholera , Burkholderia pseudomallei , and Mycobacterium tuberculosis [ 40 ]. Over the past years, the synthesis and the study of synthetic or semi-synthetic selenium-containing derivatives has attracted a steadily growing interest amongst organic chemists, medicinal chemists, and biologists [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, selenium-catalysed routes for the oxidation of organic compounds including, among others, alkenes [50][51][52], alcohols [50,53], alkynes [50], and carbonyl derivatives [50] have been developed. Additionally, biologically relevant selenium-catalysed thiol-disulfide interconversions have been widely investigated over the past few years [54][55][56][57][58][59][60][61].…”
Section: Oxidation With Hydrogen Peroxidementioning
confidence: 99%
“…Notably, selenocarbamates bearing hydroxy‐ and amino‐ functionalities 63 l – o were efficiently obtained through the selective carbamoylation of the SeH group (Scheme 31). [84] Selenocarbamates exhibit remarkable thiol‐peroxidase‐like catalytic properties. Studies on the reaction mechanism suggested an unprecedented path involving a peroxide‐driven transcarbamoylation reaction engendering catalytically active selenolate anions.…”
Section: Synthetic Applications Of Selenolsmentioning
confidence: 99%
“…Studies on the reaction mechanism suggested an unprecedented path involving a peroxide‐driven transcarbamoylation reaction engendering catalytically active selenolate anions. Therefore, because of the reactivity of their selenium‐carbon bond, selenocarbamates act as unconventional equivalents of selenolate anions [84] …”
Section: Synthetic Applications Of Selenolsmentioning
confidence: 99%
See 1 more Smart Citation